1985
DOI: 10.1055/s-2008-1059781
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Division of Small Intestine: A Surgical Possibility for Children with the Very Short Bowel Syndrome

Abstract: Surgical approach to short bowel syndrome has been dealing with two major problems: lack in absorptive surface and dysfunction of the peristalsis of the widely distended loop above the anastomosis. In those children having a very short intestine, one is reluctant to either resect or reduce the diameter of this loop. Bianchi, followed by Boeckman and Traylor, described a procedure of loop lengthening by dividing it longitudinally. Their procedure has the advantage of restoring normal peristalsis without losing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The alternative proposed is waiting until no further advancement in feeding can be achieved. 52,56 Variations in the proposed "waiting time" have ranged from 4 to 6 weeks of stability to 6 months (in children) or 2 years (in adults) in which no further advancement is made in enteral tolerance. No clear evidence for superiority of either approach exists; however, unnecessary intervention may lead to complications and we therefore choose to err on the side of caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative proposed is waiting until no further advancement in feeding can be achieved. 52,56 Variations in the proposed "waiting time" have ranged from 4 to 6 weeks of stability to 6 months (in children) or 2 years (in adults) in which no further advancement is made in enteral tolerance. No clear evidence for superiority of either approach exists; however, unnecessary intervention may lead to complications and we therefore choose to err on the side of caution.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits attributed to the lengthening procedure have included improved fat and/or d-xylose absorption, prolongation of transit time, and catch-up growth. [43][44][45][46][47][48][49][50] Absorptive studies have shown improvement after the Bianchi procedure, but they have been conducted in only a limited number of patients and some have suggested that the increased enteral tolerance is merely a result of hyperphagia, less bacterial overgrowth by eliminating the bowel dilation, and the natural bowel adaptation process. 51 Although we attribute the improvements in our patients to the surgery because we first maximized adaptation with dietary manipulations, we acknowledge the limitations of this study related to the absence of objective measures of improved absorption.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the files of children who have had LILT by Bianchi's technique modified by Aigrain [4] from 1980 to 2003. The indication for LILT was patients who do not begin progressive adaptation to enteral nutrition (EN) after the ablative surgery and who are believed to have refractory SBS.…”
Section: Methodsmentioning
confidence: 99%
“…For the increase of the area of absorption growth of neomucosa, mucosal autotransplantation, intestinal lengthening and small bowel transplantation have been performed (Grant 1999;Goulet and Ruemmele 2006). Concerning the surgical techniques, apart from intestinal loop lengthening advised by Bianchi (1980), which had been successfully used on an infant by Boeckman and Traylor (1981) and was modifi ed by Aigrain et al (1985), intestinal transplantation appears to be the only alternative for patients who have developed signifi cant liver disease (no cirrhosis) related to short bowel syndrome (Fishbein et al 2003). Certainly, all these procedures have controversial outcomes and are still at different experimental levels.…”
Section: Discussionmentioning
confidence: 99%